Profitability and Working Capital Management Nexus: Evidence from Food & Personal Care Products Sector Firms Listed on Pakistan Stock Exchange - DR. MUMTAZ HUSSAIN SHAH; FAYYAZ KHAN (Journal of Business & Tourism, 2021)
Working capital management (WCM) usually have an essential role to play in a firm’s overall performance, especially those of manufacturing sector. The key aim of the current research work is to find the empirical association amid profitability and working capital management of the Food & Personal Care Product sector Pakistani firms. Eight companies are selected randomly as a sample from the firms listed on Pakistan Stock Exchange. Secondary data for six years, that is, 2010 - 2016 is gathered from the financial reports of these companies and evaluated through Pearson correlation coefficient and regression analysis techniques, using STATA software. The results prove that Return on Assets (ROA) is negatively correlated with Average Collection Period (ACP) and positively correlated with Inventory Turnover in Days (ITID), Average Payment Period (APP), Current Ratio (CR) and Sales Growth (SG). All the relationships are significant except ITID and SG ones.